Representação e armazenamento de dados cadastrais 3D em banco de dados geográficos - Holzschuh, Marcelo Leandro [UNESP] (2013)
There is a global concern about the needs of land record, including the 3D cadastre. This thesis presents some definitions of the Multipurpose Cadastre focusing on 3D volumetric storage parcels, and one of its fundamental pillars that is the geographic database. The storage and retrieval of data are fundamental steps to the Multipurpose Cadastre, and which the necessity of cadastre manipulate complex structures such as overlapping property (public or private), underground cables and pipelines, appears to concern the storage form, both as geometric their topological relations. In this context, models are used to represent data to assist the development of geographic database and, between them, are the Formal Structure of 3D data, the Tetrahedrons Network, a Simplified Model Space and Representation by Borders, which was used this article. The B-Rep method is used to represent the solid object surface. From this method, a modeling for the Geographic Data Base PostgreSQL was developed and its space extension PostGIS, with goal of to store and to recoup volumetric cadastral objects. The potential of the B-Rep model was observed in the representation of 3D objects cadastral, which already was used in similar areas for representations 3D data. Through the experiments it was possible to prove the unequivocal identification of the parcel of property, the court and the industry, with its three-dimensional geometry, respectively. These results enable the integration between the recording and registration of three-dimensional plots.